IMPROVING FOOD SECURITY AND LIVELIHOODS: EMPOWERING SMALL FARMERS THROUGH CLIMATE-RESISTANT AGRICULTURE PRACTICES AND MARKET ACCESS STRATEGIES - Syariani Br Tambunan; Muhammad Yassir (CV Naskah Aceh, 2023)
Food security and the welfare of small farmers are two crucial issues in facing climate change and global market challenges. To overcome this problem, an environmentally friendly and adaptive agricultural approach is needed. This abstract discusses a study that aims to improve food security and the livelihoods of small farmers through empowerment with two main approaches. First, this research will analyze and identify climate-resistant agricultural techniques that are appropriate to local conditions. By implementing environmentally friendly practices, small farmers can face the impacts of climate change and reduce their vulnerability to natural disasters. Second, this study will explore effective market access strategies. Better access to markets will provide opportunities for small farmers to increase their income and strengthen their livelihoods. This strategy includes the use of information technology, partnership networks, and skill building in marketing. It is hoped that the results of this research can provide guidance for stakeholders in formulating policies and programs that focus on food security and the welfare of small farmers. Thus, agriculture can be a key driver in achieving environmental and social sustainability in the future.